Eligibility Determination for Intravenous Thrombolysis Based on Radiology Interpretation Report of the Head CT Scan in Patients with Acute Ischemic Stroke. Issue 4 (9th September 2013) - Hassan, Ameer E.; Majidi, Shahram; Janjua, Nazli A.; Chaudhry, Saqib A.; Tekle, Wondwossen G.; Grigoryan, Mikayel; Qureshi, Adnan I.
ABSTRACT OBJECTIVE To evaluate the variability of determining eligibility for intravenous thrombolysis (IV t‐PA) by a stroke team interpretation of computed tomographic (CT) scan of the head versus review of the radiology interpretation (presented in final report) in patients with acute ischemic stroke. METHODS We compiled a database of all IV t‐PA‐treated ischemic stroke patients at our academic institution based on the stroke team's CT scan interpretation. The CT scan reports of 171 patients were reviewed by an independent board‐certified vascular neurologist who was blinded to clinical information except that all patients were being considered for IV t‐PA to determine their eligibility for thrombolysis. The reviewer's responses were then compared with the treating team's decision to identify discrepancies, and the impact of the discrepant decisions on clinical outcome including 24‐hour National Institute of Health stroke Scale (NIHSS) score and discharge modified Rankin scale (mRS), symptomatic hemorrhage (sICH), and asymptomatic hemorrhage (aICH). We compared the outcomes of patients who received IV t‐PA despite cautionary neuroradiologist interpretation and placebo‐treated patients from NINDS t‐PA study. RESULTS The independent reviewer decided to treat with IV t‐PA 123 patients (72%) after reviewing the radiology reports. The rate of NIHSS score improvement (52.0% vs. 62.5%, P = .22) was not different between patients in whom IV t‐PA should or should not have been used based on radiology reports. Favorable clinical outcome defined by mRS of 0‐2 at discharge (50.4% vs. 47.9%, P = .77) and in‐hospital mortality (15.6% vs. 12.5%, P = .61) were similar between the 2 groups. Favorable outcome (discharge or day 7‐10 mRS 0‐2) was significantly higher in patients who received t‐PA compared with placebo‐treated patients (48% vs. 28%, P = .006). CONCLUSION Our study demonstrates that administering IV t‐PA to patients based on the stroke team's interpretation of the CT scan versus review of the radiology interpretation does not lead to significant differences in clinical outcome, aICH, or sICH.